Incidence of cancer among ferrochromium and ferrosilicon workers: an extended observation period. Issue 1 (January 1990) - Langård, S; Andersen, A; Ravnestad, J
Abstract : Results are presented of a cohort study on the incidence of cancers and crude death rates in ferrochromium and ferrosilicon workers. The whole cohort was observed from 1 January 1953 to 31 December 1985. Two sets of results are presented; one restricted to workers first employed before 1960 and one to workers first employed before 1965. The latter cohort consists of 1235 workers. The total mortality in the whole cohort was low (SMR = 81) as was the overall incidence of cancers (SIR = 84). There was an overall deficit of deaths and cases of cancer in the ferrosilicon group. An excess of lung cancer (SIR = 154) and cancer of the prostate (SIR = 151) was observed in the ferrochromium workers employed before 1965. Cancer of the kidney was also in excess (SIR = 273) in the ferrochromium group, with a mean "latency time" of 39 years. Two cases of malignant melanomas had occurred versus 0.19 expected in a small subgroup of workers in electrical shops and an electric power station.